L-Cysteine-capped CdTe Quantum Dots Based Fluorescence Quenching Method for Determination of Chloroamphenicol - Mao, Yongqiang; Li, Na; Han, Ye; Ning, Baoan; Gao, Zhixian; Zhou, Zhijiang (Asian Journal of Chemistry, 2012)
L-Cysteine-capped CdTe quantum dots (QDs) with a narrow, symmetric emission spectrum was synthesized in aqueous medium. Based on the fluorescence quenching of CdTe quantum dots, a simple, rapid and sensitive method was developed for the quantitative determination of chloroamphenicol. Under optimum conditions, the calibration plot of the relative fluorescence intensity with the concentration of chloroamphenicol was linear in the range from 5 to 40 μg mL-1 with the correlation coefficient of 0.9963. The limit of detection was 50 ng mL-1. The content of chloroamphenicol in pharmaceutical tablet were determined by the proposed method and the results agreed with the claimed value. In addition, the possible fluorescence quenching mechanism was also discussed.